Kompetensi Informatik Perawat di Rumah Sakit Pemerintah Tipe C - Gusrina Komara Putri (Indonesian Journal of Nursing Scientific, 2025)
Background: Digital transformation in hospitals requires nurses to possess informatics competency to support patient safety and high-quality documentation. Objective: To describe nurses’ informatics competency in hospitals using the Self-Assessment of Nursing Informatics Competencies Scale (SANICS).. Methods: A cross-sectional survey with univariate analysis was conducted using secondary data from 220 nurses. SANICS includes 30 items (total score 30–150; higher scores indicate better competency) across five subscales. Analyses included descriptive statistics and internal consistency (Cronbach’s alpha). Results: The mean total SANICS score was 87.98 (SD 19.57). The overall mean per item was 2.93 (scale 1–5), suggesting a moderate level of competency. The lowest subscale mean per item was Applied computer skills: clinical informatics (ACS) (2.60), while the highest was Basic computer knowledge and skills (BCKS) (3.03). Internal consistency of SANICS was excellent (alpha 0.971). Conclusion: These findings highlight the need to strengthen applied clinical informatics skills through continuing training, unit-based mentoring, and organizational support to enhance the integration of information systems into nursing practice.